(untitled) (Bangladesh Journal of Child Health, 2020)
Background: Nutritional status is a positive health indicator. Malnutrition is a major health problem which is associated with high morbidity and mortality of under 5 children. Factors associated with socio-economic status, mother’s education, hygiene, incidence of infectious diseases are the important determinants of malnutrition. Materials & Methods: This was a cross-sectional study. Anthropometric measurements and other data of 706 under 5 children were collected purposively during the period of May 2015 to April 2016. Results: In this study, mean age of the under 5 children was 34.61±5.4 months, male was 50.7% and female was 49.3%. This study revealed that 49% of children were underweight, 39% were stunted and 10.5% were wasted. The multivariate analysis found that mother’s education, poor socio-economic status and associated diseases had significant association with nutritional status of under 5 children. However, occupational status of child’s mother found no significant association on nutritional status. Conclusion: The prevalence of malnourished children in rural community in this study was found very high. Of them, underweight children was higher than wasted and stunted children. Bangladesh J Child Health 2020; VOL 44 (2) :87-91